Halal Food Certification and Sustainability Performance: A Conceptual Paper - Handayati, Puji; Rochayatun, Sulis; ., Meldona (KnE Social Sciences, 2024)
This paper hypothesizes that Halal Food Certification increases and enhances sustainability performance through a conceptual framework highlighting their connectivity. Many studies focus on Halal Food Certification with the business performance from various perspectives, but more research is required that explicitly studies certification and sustainability. Regarding the methodology, secondary sources related to topics and keywords have been implemented. This research refers to the guidelines for implementing halal certification based on quality management as a basis to be discussed in the Halal Industry. According to a literature review, Halal Food Certification could increase sustainability in three aspects: economic, social, and environmental. This study’s theoretical foundations can facilitate further in-depth investigation into both elements. Given their conceptual nature, the framework should undergo empirical testing. Keywords: Halal Food Certification, sustainability performance, conceptual framework